The concept of “religiosity” in the writings of L. P. Karsavin - Anna Shekhorina (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2021)
This article presents the results of the study of the concept of “religiosity” in the writings of Lev Platonovich Karsavin (1882–1952). As a result of a comparative analysis of the texts of writings of various types (dissertation, medieval studies, historiosophy, philosophy studies), the peculiarities of understanding the concept of “religiosity”, as well as its evolution, were revealed. Religiosity is the main object of study in various writings of Karsavin. In his early works, L.P. Karsavin still does not differentiate the concepts associated with the study of religiosity. In his doctoral dissertation “Foundations of medieval religiosity in the XII–XIII centuries, mainly in Italy”, L. P. Karsavin not only propose a detailed defi nition of the concept of “religiosity”. He proposed a system of conceptual apparatus, give defi nitions to such concepts as “mysticism”, “faith”, “metaphysical”, “religious fund”, “the average man”. According to L. P. Karsavin religiosity is state of mind, “mental structure”. Karsavin seeks to group specifi c manifestations of religious life around several main systems, namely polytheistic, dualistic, monotheistic, pantheistic, which characterise the main types of religious life. In historiosophical works, the ideas of L. P. Karsavins become more abstract. The concept of “religiosity” is considered as a fundamental criterion for the study and classifi cation of culture. In later works on philosophy, the idea of the fundamental signifi cance of religiosity in human life is developed.